Proccedings of International Scientific Conference "RURAL DEVELOPMENT 2017" 2018
DOI: 10.15544/rd.2017.079
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Productive and Environmental Efficiency of Slow-Release Fertilizers in Integrated Production of Napa Cabbage Depending on Application Method

Abstract: The study aimed to assess the suitability of slow-release fertilizers in cultivation of napa cabbage in the integrated production system. The objective was realized on the basis of a strict field experiment set up on soil with granulometric composition of light loam. The dose of fertilizer was the first experimental factor, and the fertilizer application was the second factor. The slow-acting fertilizer was applied under each plant during planting of seedlings and in the second variant. The fertilizer was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…These authors draw attention to the major potential of slow-release fertilizers in the process of reducing water eutrophication and greenhouse gas emissions to the atmosphere. The increase in the potential of using nitrogen in the form of slow-release fertilizers was also observed by Niemiec et al [29,32] and Purnomo et al [41]. The results of our own research also indicate the suitability of slow-release fertilizers in the process of optimizing nitrogen fertilization.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…These authors draw attention to the major potential of slow-release fertilizers in the process of reducing water eutrophication and greenhouse gas emissions to the atmosphere. The increase in the potential of using nitrogen in the form of slow-release fertilizers was also observed by Niemiec et al [29,32] and Purnomo et al [41]. The results of our own research also indicate the suitability of slow-release fertilizers in the process of optimizing nitrogen fertilization.…”
Section: Resultssupporting
confidence: 86%
“…In other sites, the variability ranged from about 11 to 15%, and no effect of the applied fertilization strategy on this parameter was found. Niemiec et al [29] found that increasing the dose of slow-release fertilizers applied to roots in the cultivation of Chinese cabbage (nappa cabbage) resulted in an increased difference in unit weight of individual plants. Similar results were obtained by Niemiec et al [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation